Necesidades motivacionales de los atletas 400 metros planos de la categoría juvenil vinculados al InderBuenaventura (2021)
Motivation in sport leads to good or poor results according to the discipline in which you perform. This study was carried out with the aim of describing the motivational needs of athletes 400 meters flat of the youth category linked to the Institute of Physical Education, Sport and Recreation of the Buenaventura Special District of valle Del Cauca department; which was carried out through the descriptive quantitative method, with which it was obtained through mcClellan's Motivational Needs Questionnaire, the predominant motivational needs of each athlete I participate in, where three subcategories stand out: Achievement, Power and Affiliation, was applied to a sample of 17 athletes. From the data obtained it is possible to show that in most athletes predominates the motivational need for achievement, which leads to optimal athletic performance and thus obtain better results, taking into account that teamwork is important to them.